ANALYSIS OF ENGLISH LEARNING FROM THE PRAGMATIC SIDE - Ishankulova, Diyora (Журнал иностранных языков и лингвистики, 2023)
Just as there is a biosphere in which living beings live and develop, there is an association space in which the human being as a social being is the focus. This sociosphere is simply a set of social and cultural norms that tell you how to behave in a particular social group. When someone decides to learn a foreign language or, moreover, to learn a new language system, they need to study certain social and cultural norms that govern the communicative exchanges that make up the sociosphere.